2015
DOI: 10.1007/s11240-015-0883-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, molecular characterization and functional analysis of a putative R2R3-MYB transcription factor of the phenolic acid biosynthetic pathway in S. miltiorrhiza Bge. f. alba

Abstract: The water-soluble phenolic acids of S. miltiorrhiza Bge. f. alba can protect against herbivores or pathogenic bacteria and have numerous pharmacological activities that are beneficial to human health. The main phenolic acids in S. miltiorrhiza, including rosmarinic acid and salvianolic acid B, are derived from the rosmarinic acid biosynthetic pathway, which has been partially characterized. However, little is known about the endogenous bHLH and MYB transcription factors that function in this pathway. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…For example, SmMYB39 repressed phenolic acids biosynthesis when overexpressed in S. miltiorrhiza [ 17 ], whereas SmPAP1, the other member of MYB TFs, is involved in enhancing phenolic acid production by interacting with bHLH TFs SmMYC2 and activating genes encoding key enzymes in S. miltiorrhiza Bge. f. alba [ 18 ]. Zhou et al found JAZ-interacting TFs SmMYC2a and SmMYC2b positively regulate the biosynthesis of tanshinones and salvianolic acid B [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, SmMYB39 repressed phenolic acids biosynthesis when overexpressed in S. miltiorrhiza [ 17 ], whereas SmPAP1, the other member of MYB TFs, is involved in enhancing phenolic acid production by interacting with bHLH TFs SmMYC2 and activating genes encoding key enzymes in S. miltiorrhiza Bge. f. alba [ 18 ]. Zhou et al found JAZ-interacting TFs SmMYC2a and SmMYC2b positively regulate the biosynthesis of tanshinones and salvianolic acid B [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response, many studies have since focused on increasing this species phenolic acid contents by either overexpressing or suppressing its transcription factors or key enzyme genes within the relevant metabolic pathways. For example, the overexpression of SmTAT , SmC4H , SmHPPR , AtPAP1 , AtEDT1 , and SmPAP1 induced a substantial accumulation of phenolic acids in the transgenic S. miltiorrhiza ( Zhang Y. et al, 2010 ; Xiao et al, 2011 ; Hao et al, 2016 ; Liu Y. et al, 2016 ), whereas the downregulation of SmMYB39 , SmHPPD , SmCCR1 , or SmCHS all increased the content of phenolic acids ( Xiao et al, 2011 ; Wang et al, 2012 ; Zhang et al, 2013 ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some MYB families have been determined to play important roles in wood formation and development in some tree species. For instance, AaMYB2 is involved in anthocyanin biosynthesis in anthurium spathes and leaves, while PtMYB4 from Pinus taeda was reported to regulate phenolic acid biosynthesis (Hao et al, 2016;. In addition, an R2R3 MYB TF MYB134 was found to be coinduced with PA biosynthetic genes in poplar after several kinds of stress treatments (Mellway et al, 2009).…”
Section: Discussionmentioning
confidence: 99%